2023
DOI: 10.1159/000535302
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vitamin D with Severity and Outcome of COVID-19: Clinical and Experimental Evidence

Georgios Renieris,
Spyros Foutadakis,
Theano Andriopoulou
et al.

Abstract: Introduction: The role of vitamin in COVID-19 remains controversial. We investigated the association between endogenous vitamin D and the severity of COVID-19 as well as the mechanisms of action of vitamin D supplementation. Methods: 25(OH)D3 in serum was associated with disease severity and outcome in 190 COVID-19 patients. In a COVID-19 animal model using intravenous injection of plasma from patients with COVID-19 ARDS into C57/BL6 mice, mice were treated with 0.25μg human 1,25(OH)D3 or vehicle. Mice were sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The association between NLR and vitamin D is not yet fully understood. The study of Renieris et al [15] and Pimentel et al [51] showed that NLR was inversely associated to vitamin D levels, while Gulcan et al [58] did not identify any correlation between the two parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association between NLR and vitamin D is not yet fully understood. The study of Renieris et al [15] and Pimentel et al [51] showed that NLR was inversely associated to vitamin D levels, while Gulcan et al [58] did not identify any correlation between the two parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies analyzed the relationship/role of vitamin D levels/supplementation in incidence/severity of respiratory tract infections, including COVID-19 [7][8][9]. Studies regarding the relationship between vitamin D and COVID-19 clinical and laboratory profile or disease outcomes, mainly focused on adult patients and often showed conflicting results [10][11][12][13][14][15][16][17][18][19][20][21][22]. A series of studies identified a negative correlation between vitamin D and NLR and CRP [12,13], while other studies did not identify any correlation between them [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation